CHANGE OF FUNCTIONAL PROPERTIES OF WHEY PROTEIN - Mowafak M Ali Al-Obydi (Mesopotamia Journal of Agriculture)
Sweet and sour (salted or unsalted) whey protein concentrates were used after acetylation with acetic anhydride or succinylation with succinic anhydride at 0.5 % to improve the functional properties of dough. The addition of sweet salted whey protein concentrates and acetylated at 0.5% and added at 15% to the dough resulted in highest values of loaf volume and spongyness while when used at 40% it gave an unacceptable results. This indicates that addition of these concentrates was best at 15% of the dough followed by 30% then by 40% for all the treatments. Sensory evaluation indicates that the loaf made from doughs with the addition of ace- tylated and succinylated at 0.5% and added at 15% to the dough gave the best res ults for all the studied properties followed by 30% addition while at 40% addition was the lowest and the loaf was unacceptable.